2018
DOI: 10.1016/j.psychres.2018.06.039
|View full text |Cite
|
Sign up to set email alerts
|

Immigrants and mental disorders in the united states: New evidence on the healthy migrant hypothesis

Abstract: Consistent with the healthy migrant hypothesis, immigrants are less likely to come from families with psychiatric problems, and those who migrate after childhood-when selection effects are most likely to be observed-have the lowest levels of psychiatric morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 44 publications
4
36
0
1
Order By: Relevance
“…Our analysis showed that the ethnic concentration variable had a negative association with mental illness risk. Similar findings were found in an epidemiological study by Salas-Wright et al (2018). Their results were based on a population survey of 36,309 adults consisting of immigrants and individuals born in the US.…”
Section: Discussionsupporting
confidence: 87%
“…Our analysis showed that the ethnic concentration variable had a negative association with mental illness risk. Similar findings were found in an epidemiological study by Salas-Wright et al (2018). Their results were based on a population survey of 36,309 adults consisting of immigrants and individuals born in the US.…”
Section: Discussionsupporting
confidence: 87%
“…Research on alcohol misuse is greatly needed among Hispanic populations in general because studies suggest that the consequences of alcohol misuse are often more severe for Hispanics compared to non‐Hispanic Whites. Specifically, although Hispanics may be less likely to drink than non‐Hispanic Whites (Goings et al, 2019; Salas‐Wright et al, 2018), Hispanics who choose to drink, especially young Hispanic adults (Cano et al, 2015; Venegas, Cooper, Naylor, Hanson, & Blow, 2012), tend to consume higher volumes of alcohol and experience more alcohol‐related problems (e.g., liver disease, legal citations from drunk driving, aggression, loss of employment) than non‐Hispanic Whites (Mulia, Ye, Greenfield, & Zemore, 2009; Substance Abuse and Mental Health Services Administration, 2013). Studies also show that Hispanic immigrants report lower rates of alcohol use than their U.S.‐born Hispanic counterparts (e.g., Greene & Maggs, 2018; Salas‐Wright et al, 2018)—where Hispanics from Puerto Rico and Mexico report the highest levels of alcohol use, and those from Cuba report the lowest (see NIAAA, 2018, for a breakdown by country).…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Migrants' countries of origin, reasons for immigration, time spent in the new country of residence and personal situations vary, and their health has no universal pattern. Some migrant groups have better health than natives and lower mortality [3,4,5,6] and they purchase less prescribed drugs [7].…”
Section: Introductionmentioning
confidence: 99%